Ethnomathematics E-learning Teaching Material Development: Student-Oriented Problem-Solving Ability - Rokhmah, Na'immatur; Yaniawati, R. Poppy; Supianti, In In; Bin Ku Mahamud, Ku Hafisal (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2024)
The purpose of this study is to produce e-learning-based ethnomathematical teaching materials and analyze students' problem-solving abilities when students learn to use ethnomathematical-based teaching materials that have been developed. This research is the development of R&D (Research & Development) involving 30 students of SMK MVP Ars International Bandung by applying the Plomp model. The stages of the Plomp model are initial investigation, design, realization, evaluation and revision, and implementation. So, instruments are material validation sheets, interviews, questionnaires, and problem-solving ability tests. This research's data analysis uses the Chocran, average comparison, and N-gain tests. The results of this research are: (1) SPLDV teaching materials in e-learning-based Ethnomathematics are classified as feasible on the evaluation of material, and media experts, as well as student responses, (2) Problem-solving abilities used in e-learning, are included in the high category. In this way, SPLDV teaching materials in e-learning-based ethnomathematics mean that students are more interested in learning and can be a reference for teachers in improving students' mathematical problem-solving abilities.